2008
DOI: 10.1002/qua.21563
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic decoupling of the reaction coordinate

Abstract: ABSTRACT:When the dynamics is constrained by adiabatic invariance, a reactive process can be described as a one-dimensional motion along the reaction coordinate in an effective potential. This simplification is often valid for central potentials and for the curved harmonic valley studied in the reaction path Hamiltonian model. For an ionmolecule reaction, the action integral ͗P ͘ ϭ ͑1/2͒͛P d is an adiabatic invariant. The Poisson bracket of ͗P ͘ 2 with Hamiltonians corresponding to a great variety of longrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…As pointed out by Bates 61 and by Schlier, 62 the cyclic action integral Ip θ dθ, where p θ is an angular momentum, is an adiabatic invariant of the problem; that is, the reaction coordinate is adiabatically decoupled from rotation. Recent research 63,64 has shown that the Poisson bracket of the adiabatic invariant is proportional to p r µ r -3 for the ion-dipole interaction and to p r Q r -4 for the ion-quadrupole case. This short-range behavior of the Poisson bracket implies that the quality of the adiabatic approximation is expected to be quite good, at least at asymptotically large values of r. However, because it also increases linearly with the translational momentum p r , the validity of the adiabatic separation becomes questionable at high translational energies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As pointed out by Bates 61 and by Schlier, 62 the cyclic action integral Ip θ dθ, where p θ is an angular momentum, is an adiabatic invariant of the problem; that is, the reaction coordinate is adiabatically decoupled from rotation. Recent research 63,64 has shown that the Poisson bracket of the adiabatic invariant is proportional to p r µ r -3 for the ion-dipole interaction and to p r Q r -4 for the ion-quadrupole case. This short-range behavior of the Poisson bracket implies that the quality of the adiabatic approximation is expected to be quite good, at least at asymptotically large values of r. However, because it also increases linearly with the translational momentum p r , the validity of the adiabatic separation becomes questionable at high translational energies.…”
Section: Discussionmentioning
confidence: 99%
“…When the reaction coordinate is adiabatically decoupled from the bath, the dynamics is equivalent to a one-dimensional motion along the reaction coordinate in an effective potential. [62][63][64] The equation of motion obeys Jacobi's form of the least-action principle, which is particularly simple when the dynamics is one-dimensional. [63][64][65] This principle asserts 57,66 that the actual trajectory between two points r 1 and r 2 minimizes the integral ∫ r1 r 2 ε 1/2 dr.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simple model computations are reviewed in ref ; see also refs . Propensity rules relating states and channels are discussed in refs and and references therein with important earlier work by Troe and Quack …”
Section: Introductionmentioning
confidence: 99%